PD-L1 Is Not Constitutively Expressed on Tasmanian Devil Facial Tumor Cells but Is Strongly Upregulated in Response to IFN-γ and Can Be Expressed in the Tumor Microenvironment - Flies, Andrew S.; Lyons, A. Bruce; Corcoran, Lynn M.; Papenfuss, Anthony T.; Murphy, James M.; Knowles, Graeme W.; Woods, Gregory M.; Hayball, John D. (Frontiers in Immunology, 2016)
The devil facial tumor disease (DFTD) is caused by clonal transmissible cancers that have led to a catastrophic decline in the wild Tasmanian devil (Sarcophilus harrisii) population. The first transmissible tumor, now termed DFT1, was first discovered in 1996 and has been continually transmitted to new hosts for at least 20 years. In 2015 a second transmissible cancer (DFT2) was discovered in wild devils, and the DFT2 is genetically distinct and independent from the DFT1. Despite the estimated 136,559 base pair substitutions and 14,647 insertions/deletions in the DFT1 genome as compared to two normal devil reference genomes, the allograft tumors are not rejected by the host immune system. Additionally, genome sequencing of two sub-strains of DFT1 detected greater than 15,000 single-base substitutions that were found in only one of the DFT1 sub-strains, demonstrating the transmissible tumors are evolving and that generation of neoantigens is likely ongoing. Recent evidence in human clinical trials suggests that blocking PD-1:PD-L1 interactions promote anti-tumor immune responses and is most effective in cancers with a high number of mutations. We hypothesized that DFTD cells could exploit the PD-1:PD-L1 inhibitory pathway to evade anti-tumor immune responses. We developed recombinant proteins and monoclonal antibodies to provide the first demonstration that PD-1 binds to both PD-L1 and PD-L2 in a non-placental mammal and show that PD-L1 is upregulated in DFTD cells in response to IFN-γ. Immunohistochemistry showed that PD-L1 is rarely expressed in primary tumor masses, but low numbers of PD-L1+ non-tumor cells were detected in the microenvironment of several metastatic tumors. Importantly, in vitro testing suggests that PD-1 binding to PD-L1 and PD-L2 can be blocked by monoclonal antibodies, which could be critical to understanding how the DFT allografts evade the immune system.